PENGARUH TINGKAT PENDIDIKAN, TINGKAT PENDAPATAN, DAN PENDAMPINGAN ORANG TUA, TERHADAP CAPAIAN PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN DI KECAMATAN METRO PUSAT - Ismatul Izza Al Iftitah; Amir Syamsudin (Jurnal Kajian Anak (J-Sanak), 2023)
research aimed to determine the effect of education, income, and parental assistance on the cognitive development of 5-6-year-olds children in Metro Pusat Sub-district. The research employed a quantitative method and a purposive sampling technique comprising 338 subjects as a sample. The study subjects were parents of 5-6-year-olds children attending 21 kindergartens in the Metro Pusat Sub-district. The subject criteria were children whose parents are employed. The study’s findings compared t-value, t-table, p-value, and sig value. The data processing results indicated that the t-statistical value of parental education level and parental income level was more significant than t table 1.960, and the sig value was less than 0.05. This indicated that parental education and income affected the cognitive development achievement of 5-6-year-olds children in Metro Pusat Sub-district. In addition, parental assistance possesses a statistical t-value less than 1.960 and a sig value greater than 0.05. This indicated that parental assistance did not affect the cognitive development of Metro Pusat Sub-district children aged 5 to 6 years. The combined effect of education, income, and familial support has a t-table value of greater than 1.960 and a sig value of less than 0.05. This revealed that education, income,